Perubahan Iklim dan Suku Bangsa Minoritas di Filipina: Pengalaman dan Pelajaran dari Suku Bangsa Ifugao untuk Masyarakat Asia Pasifik - Ekoningtyas Margu Wardani (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2014)
This paper discusses the global issue of climate change in relation with the life of indigenous people living in northern Luzon of the Philippines, Ifugao Community. The finding reveals that in a way of Ifugao People face profound global problems of climate change, the people cling to their own local knowledge. History shows that for thousands of years Ifugao farmers could adapt to their environment. This includes resiliency to the changes of climate. It is hoped that based on the Ifugao experiences, lesson learned could be drawn for other indigenous communities elsewhere, particularly in Asia Pacific Region which have similar problems.Keywords: Ifugao, climate change, ethnography, local wisdom.